2002
DOI: 10.1248/jhs.48.560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acellular Pertussis Vaccine Against Various Strains of Bordetella Pertussis in a Murine Model of Respiratory Infection.

Abstract: The protective effects of an acellular pertussis vaccine were investigated in a murine model of respiratory infection (aerosol challenge model) with various strains of Bordetella pertussis (B. pertussis) as challengers. There were no significant differences in terms of the time course of increases in numbers of bacterial cells in mouse lungs after aerosol challenge among the tested phase I strains. The vaccine had a strong protective effect against of B. pertussis strain Tohama the phase I strain used for prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…Taking together, based on our results and those on vaccinated mice previously published [9] , [10] , [11] , [12] , [13] we propose that of the three Prn variants, Prn1 binds most efficiently to the host cells, explaining its predominance in unvaccinated populations. Vaccination with Prn1-containing vaccines may have shifted the competitive balance between Prn variants allowing non-vaccine types Prn2 and Prn3 to emerge.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Taking together, based on our results and those on vaccinated mice previously published [9] , [10] , [11] , [12] , [13] we propose that of the three Prn variants, Prn1 binds most efficiently to the host cells, explaining its predominance in unvaccinated populations. Vaccination with Prn1-containing vaccines may have shifted the competitive balance between Prn variants allowing non-vaccine types Prn2 and Prn3 to emerge.…”
Section: Discussionsupporting
confidence: 76%
“…Antigenic divergence has occurred between vaccine strains and clinical isolates with respect to several vaccine components; Ptx, Prn, and fimbriae [3] , [6] , [7] , [8] . Further variation in Ptx and Prn has been shown to affect vaccine efficacy in a mouse model [9] , [10] , [11] , [12] , [13] . In addition to antigenic variation, increased Ptx production has been associated with the resurgence of pertussis [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus variation in these proteins may affect immune recognition and hence strain fitness. Significantly, antigenic divergence has been observed between circulating strains and vaccine strains with respect to these five proteins and several studies in mouse models have provided evidence this affects vaccine efficacy [33] , [34] , [35] , [36] , [37] . Besides antigenic divergence between circulating strains and vaccine strains, another adaptive phenomenon may be the recent emergence of strains with increased Ptx production [5] , [26] , [38] , [39] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been proposed that reemergence may be due to antigenic shift in the circulating strains in response to pertussis vaccines. Previous studies (11,23,31,35) reported that polymorphisms of the pertussis toxin A subunit (PtxA) and pertactin (Prn) in circulating B. pertussis strains in the Netherlands distinguished these proteins from those present in the pertussis vaccine (8,30), and these polymorphisms have now been detected worldwide (1,3,4,6,8,12,19,26,30). Since these two proteins have been shown to be protective antigens of B. pertussis and are used as essential components of acellular pertussis vaccines, it has been proposed that the polymorphisms may confer vaccine resistance and contribute to reemergence.…”
mentioning
confidence: 96%